Perbandingan Morfometri Mandibula Belalang Phlaeoba fumosa S. dengan Ketinggian Berbeda - Nur Isya Cahyarani; Agung Budiantoro (Naturalis: Jurnal Penelitian Pengelolaan Sumberdaya Alam dan Lingkungan, 2026)
Phlaeoba fumosa is a species of grasshopper belonging to the order Orthoptera, and is often found in various terrestrial habitats, including agricultural land, forests, and grasslands. This grasshopper belongs to the herbivorous group that feeds on the leaves of various types of plants, including cultivated plants such as chillies and rice. This study aims to examine the relationship between abiotic factors and the mandible morphology of Phlaeoba fumosa grasshoppers living at different altitudes. Samples were collected using the Visual Encounter Survey (VES) method with direct capture by hand in the Merapi Valley area (±700 m above sea level) as data for highlands, and rice fields (±200 m above sea level) as data for lowlands. The abiotic factors tested included air temperature, air humidity, wind speed, soil temperature, soil pH, and light intensity. Leaf thickness was measured to determine the differences between leaves in high and low altitudes. The data were analysed using the Mann–Whitney and Spearman tests. The results showed that the mandibular rigi of grasshoppers living in highlands (449.33 ± 22.45 µm) were longer than those in lowlands (371.44 ± 55.35 µm), in response to thicker leaves due to lower temperatures and higher radiation exposure (p<0.05). Correlation analysis also showed that several abiotic factors, particularly air temperature, soil temperature, soil pH, humidity, and light intensity, were significantly related to the length of the mandibular protrusion of P. fumosa. This study reveals how environmental changes, particularly leaf thickness, drive morphological adaptations in herbivorous feeding organs.